2017
DOI: 10.1371/journal.pone.0170928
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variation and Futuristic Emission Scenario of Ambient Nitrogen Dioxide over an Urban Area of Eastern India Using GIS and Coupled AERMOD–WRF Model

Abstract: The present study focuses on the spatio-temporal variation of nitrogen dioxide (NO2) during June 2013 to May 2015 and its futuristic emission scenario over an urban area (Durgapur) of eastern India. The concentration of ambient NO2 shows seasonal as well as site specific characteristics. The site with high vehicular density (Muchipara) shows highest NO2 concentration followed by industrial site (DVC- DTPS Colony) and the residential site (B Zone), respectively. The seasonal variation of ambient NO2 over the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…On the other hand, increases in vegetation, particularly in forest cover and in water bodies, may have more positive effects on the natural environment (Trombulak and Frissell, 2000;Myhre et al, 2013;Sahim, 2018). Several previous studies have described air quality and its impact on the surrounding environment of Barddhaman (Reddy and Ruj, 2003;Gupta et al, 2009;Chatterjee, 2011;Banerjee, 2013;Palit et al, 2013;Roy et al, 2015;Chattopadhyay et al, 2017;Dey et al, 2017). Others have used remote sensing or census data to describe land use and land cover change arising from urban and industrial expansion (Sikdar et al, 2004;Chatterjee et al, 2012;Gupta and Roy, 2012;Banerjee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, increases in vegetation, particularly in forest cover and in water bodies, may have more positive effects on the natural environment (Trombulak and Frissell, 2000;Myhre et al, 2013;Sahim, 2018). Several previous studies have described air quality and its impact on the surrounding environment of Barddhaman (Reddy and Ruj, 2003;Gupta et al, 2009;Chatterjee, 2011;Banerjee, 2013;Palit et al, 2013;Roy et al, 2015;Chattopadhyay et al, 2017;Dey et al, 2017). Others have used remote sensing or census data to describe land use and land cover change arising from urban and industrial expansion (Sikdar et al, 2004;Chatterjee et al, 2012;Gupta and Roy, 2012;Banerjee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This also correlates to SO 2 pattern of distribution and similarly shows that lower NO 2 distribution at Fegge/Nupe square is due to prevalent high wind speeds and precipitation [14]. Another significant contributor of NO 2 are the industrial activities centered on upper Iweka, has been similarly observed [25,26]. Moreover, the distance from the monitoring site might equally affect the density of NO 2 concentration per unit area [22].…”
Section: Air Quality Index Evaluationmentioning
confidence: 62%
“…Long-range horizontal transport also plays a crucial role in the variation of ground level ozone concentration . Many researchers have focused on the monitoring and analysis of air pollutants and air quality in different parts of India like Kolkata, Delhi, Lucknow, Haryana, Chennai, Mumbai, Dhanbad-Jharia, Raniganj-Asansol, Durgapur and Burdwan (Lal and Patil, 2001;Jain and Saxena, 2002;Goyal and Sidhartha, 2003;Reddy and Ruj, 2003;Verma et al, 2003;Kaushik et al, 2006;Pulikesi et al, 2006;Gupta et al, 2008;Chattopadhyay et al, 2010;Dey et al, 2014Dey et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%